Bridging pedagogical innovation and practice: a literature review on ict adoption in higher education (MMIT Proceedings, 2025)
ICT adoption in higher education has revolutionized traditional paradigms of teaching and learning. Based on similar literature, this present study addresses the role of ICT in changing the pedagogy of teaching, learning engagement, and academic performance at the university level. It utilizes peer-reviewed evidence and systematic reviews within the framework of emerging trends, strengths, and weaknesses of ICT adoption. Findings confirm that although ICT enhances interactivity, flexibility, and accessibility, it also has its own limitations in digital divides, poor training, and infrastructural disabilities. The study concludes its findings by presenting best practices and recommendations on ICT adoption success in higher learning.